ПРЯМИЙ МАРКЕТИНГ У СИСТЕМІ МАРКЕТИНГОВИХ КОМУНІКАЦІЙ - Poita, Iryna (Zhytomyr Ivan Franko State University, 2025)
The article examines the role of direct marketing within the system of marketing communications and its significance for building long-term relationships between a company and its consumers. The essence of direct marketing is revealed as a set of tools that enables personalized interaction with the target audience based on individual requests, behavioral characteristics, and analytical data. The article substantiates the nature, purpose, and main tasks of direct marketing and analyzes its key channels. Particular attention is devoted to the main direct marketing instruments such as email marketing, mobile messaging, messengers, retargeting advertising, personalized social media content, chatbots, and telemarketing. Special emphasis is placed on the advantages of direct marketing, including precise targeting, flexible communication adjustments, rapid feedback, and measurability of results. It is highlighted that the effectiveness of direct marketing largely depends on data quality, the level of automation, and the company’s ability to tailor content to consumer needs. At the same time, the study outlines challenges related to the use of direct marketing tools, such as privacy issues, communication overload, and risks of declining loyalty due to irrelevant messages. The article analyzes the popularity of this method in Ukraine and identifies key problems and prospects for its development. Definitions of all elements of direct marketing are provided, and the main factors influencing its popularity, importance, and methodological diversity are determined. The goals of direct marketing for businesses and consumers are outlined, and the opportunities and challenges of its development in Ukraine are discussed. It is concluded that direct marketing is a strategic element of modern marketing communications, capable of enhancing the effectiveness of customer interaction and supporting a company’s competitiveness in a dynamic market environment.